Supply Chain Management of Icds Programme through Anganwadi and Their Impact on Child Health - Khan, Shirin; Kumar, Dilip; Singh, P R (International Journal of Computer Sciences and Engineering, 2025)
The present study was conducted at Bilaspur district of Chhattisgarh state. Total 80 Anganwadi children were survey through structured interview schedule by the researcher. It was observed that out of total 80 respondents, majority of them (76.25%) were belonged to Hindu religion, majority of them (52.50%) were belonged to scheduled caste, 55 per cent were living in pakka house, 53.75 per cent had attendance more than 20 days in a month, children’s face (78.75%) observed normally, 43.75 per cet teeth appeared white, 32.5 per cent hairs were appeared rough, 27.5, 15 and 7.5 per cent of the respondent’s nails were observed easily break down, white spot and pale respectively